Deep Sea Currents Driven by Breaking Internal Tides on the Continental Slope. Issue 12 (22nd June 2018) - Xie, Xiaohui; Liu, Qian; Zhao, Zhongxiang; Shang, Xiaodong; Cai, Shuqun; Wang, Dongxiao; Chen, Dake
Abstract: Mooring data collected on the continental slope of the South China Sea show that along‐slope deep sea bottom currents are generated when large spring internal tides (internal waves with tidal frequency) are observed, with the maximum velocity amplitude exceeding 0.15 m/s. The observations are consistent with predictions that near‐bottom breaking of internal waves can result in generation of along‐slope flows when these waves obliquely approach the slope. A linear internal tide model in one horizontal dimension with realistic topography and stratification is used to show that the breaking of internal tides is likely due to near‐critical reflection on the slope. Combining the mooring observations and the model simulation, an along‐slope near‐bottom transport of ~0.5 Sv is estimated. Along‐slope bottom flows caused by breaking internal waves potentially provide a significant way to deform continental slopes and affect deep water exchange between the marginal sea and open ocean. Key Points: Internal tides are often obliquely incident to continental slopes Internal tides break at near‐critical bottom slopes Along‐slope deep currents can be generated by breaking internal tides